ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER PADA PT. BANK CIMB NIAGA, Tbk - -, Eli Purwanti (EKONOMIA, 2020)
An alternative carried out by banks in the face of business competition is through merging between banks. This research was conducted to determine the financial performance of PT. Bank CIMB Niaga, Tbk is projected using net profit margin, return on assets, and return on equity and compares it before and after the merger between Bank Niaga and Lippo Bank in 2008 using data in the form of financial statements for the period 2005-2017. The analytical tool used includes profitability ratio analysis using net profit margin, return on assets, and return on equity before the merger for the period 2005-2007 and after the merger for the period 2008-2017, wherein the financial statement posts consist of net income after tax, sales, total assets, and total capital. The results concluded that the ratio of net profit margins, return on assets and return on equity fluctuated during the period before and after the merger. The average ratio of net profit margin, return on assets, and return on equity after the merger has decreased compared to before the merger so the proposed hypothesis is rejected. Fluctuations in the ratio of net profit margin, the ratio of return on assets, and the ratio of return on equity during the period before and after the merger due to fluctuations in net income obtained by PT. Bank CIMB Niaga, Tbk, while the total income, total assets, and total capital of the bank experienced a significant increase after the merger.